ANALISIS KEUNTUNGAN USAHA GULA AREN DI DESA WANGA KECAMATAN MOTOLING TIMUR KABUPATEN MINAHASA SELATAN - Sayow, Memey Jein; Manginsela, Elsje Pauline; Pangemanan, Paulus Adrian (AGRI-SOSIOEKONOMI, 2022)
This study aims to analyze the profits of palm sugar business in Wanga Village, East Motoling District, South Minahasa Regency. This research was carried out from November 2020 to May 2021. Sampling was carried out using a purposive sampling method, namely 10 respondents from 287 palm sugar farmers in Wanga Village. Data was collected through observation, documentation, and interviews. Data analysis used in this research is quantitative analysis, namely business profit analysis. The results showed that the large profits and R/C value obtained by all palm sugar processors when calculated with raw materials and labor, processors experienced losses. Meanwhile, if it is not calculated with raw materials and labor, processors experience large profits.